PENGELOLAAN KEUANGAN USAHA MIKRO SEKTOR KULINER DI KECAMATAN MEDAN DENAI - Isna Ardila; Irma Christiana (-)
Micro Enterprises is a business that has developed sufficiently but cannot accept subcontract work and cannot export goods. Financial management is important for micro enterprises in order to provide an overview of performance as a success and sustainability of the business. There are three indicators that can be used in terms of financial management, namely the use of budgets, recording and reporting. The research approach used a qualitative descriptive method. The sample in this study were 30 culinary sector micro-entrepreneurs in Medan Denai District. Data were collected by distributing questionnaires and conducting interviews. The results showed that the financial management of micro-business in the culinary sector in Medan District was still lacking, especially in the indicators of reporting and budget use, while for the recording of some micro-entrepreneurs they had done it but it was still in the form of simple notes.                            Keyword : Micro Enterprises, financial management